Evaluation of delamination crack tip in woven fibre glass reinforced polymer composite using FBG sensor spectra and thermo-elastic response. (July 2018) - Kakei, Ayad; Epaarachchi, J.A.; Islam, Mainul; Leng, J.
Highlights: Embedded delamination damage cannot be indicated visually. TSA method use quadrature signals provides solid evidence of extension of delamination crack. Embedding sensor technology provides excellent capability to detect delamination crack tip under axial loading. State variable SDVn fore cohesive elements are a significant indictor for detection of delamination damage. Abstract: This paper details a study which was carried out on the application of FBG sensors for investigation of delamination crack status in glass fibre reinforced composite materials. A woven glass (0/90) epoxy composite sample containing a purposely created delamination and an embedded FBG sensor was investigated to study the behaviour of delamination crack under applied axial quasi-static tensile load. The reflected spectra from FBG sensor and the thermo-elastic response using an infrared camera were recorded to detect the propagation of delamination crack tip. In addition a finite element analysis (FEA) was performed using cohesive elements to simulate delamination crack tip. It has been seen that the propagation of delamination crack tip monitored from thermal stress analysis (TSA) was consistent with the prediction of the FBG sensor response. Further it has been observed that the experimentally observed delamination damage propagation was in a good agreement with FEA simulation results.